RESEARCH ON OPTIMIZATION OF ROTOR MESHING LINE BASED ON COMPREHENSIVE PERFORMANCE INDEX (MT) - HU Rong; HE Xue Ming; YU Jia Chuan (Jixie qiangdu, 2023)
In the optimization design of twin-screw compressor line, the influence of geometric parameters on compressor performance is considered to be different. In order to judge the advantages and disadvantages of the designed profile more directly, proposed a comprehensive performance index to judge the advantages and disadvantages of the rotor profile, and designed a rotor with better profile based on the comprehensive performance index for fluid simulation and experimental verification. Compared with the original profile, the length of the contact line of the optimized profile increases slightly, the area of leakage triangle decreases, area utilization coefficient increased. But the single performance index which reflects the whole performance index is better, which also preliminarily proves the correctness of the proposed method.